(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Asonova G. A. Keywords: Russian language as foreign, communication skills, traditional teaching, grammatical and communicative game tasks. This article is devoted to the ways to activate knowledge of the Russian language as foreign through game oriented grammatical and communicative exercises. The task is to help learners to transform their communication skills from passive knowledge into active use of the language with the help of game at the initial stage of learning. Nowadays it is not enough to use only the methods of traditional learning based on the grammar-translation method or direct method The use of grammatical and communicative game tasks helps to develop critical thinking of students, improve their knowledge in situations which are authentic and close to real life.